THE IMPLEMENTATION OF WRITE-PAIR-SHARE TECHNIQUE IN TEACHING WRITING OF HORTATORY EXPOSITION TEXT - RISMA KARTIKA DEWI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2016)
In learning English as a foreign language, the learners have to be able to communicate in English. The students have to have good communication in both oral and written forms which are realized into four skills; listening, speaking, reading and writing (Depdiknas, 2006: 216). However, writing is considered as the most difficult skill for the foreign language learners or students because the students have to follow the rules of the target language to produce a good writing. Learning writing is a difficult task not only for foreign language learners, but also for natives or first language learners (Nunan, 1989: 35). Writing should be practiced and learned gradually and it needs long time to make the students skillful in writing. This skill needs particular practice to develop. As Ferguson in Celce-Murcia (2001: 4) states that writing is not acquired through studying but practicing.The problems above also occur on students of SMAN 2 Nganjuk. The students of XI IPS-1 have problems in writing composition. The English teacher of XI IPS-1 class said that most of the students show a refusal expression when they are asked to make a composition. In consequence of the students’ unwillingness, most of the students’ writing scores do not achieve the standard score.This article will expose the implementation of Write-Pair-Share (WPS) technique in teaching writing of hortatory exposition text to the XI IPS-1 of SMAN 2 Nganjuk. Write-Pair-Share (WPS) is one of Cooperative Learning (CL) technique. Slavin in Cornelius-White (2010: 138) states that cooperative learning appears to be effective across all groups and levels tested, with potentially more positive effects for students who are high achievers, who receive special education, or who come from diverse cultural and ethnic backgrounds.  Keywords: Write-Pair-Share (WPS), Writing, Hortatory Exposition Text